2014
DOI: 10.2319/121913-930.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharyngeal airway volume in adolescent patients affected by bilateral cleft lip and palate using cone beam computed tomography

Abstract: Objective: To test the null hypothesis that there were no significant differences for pharyngeal airway volumes between the adolescent patients affected by bilateral cleft lip and palate (BCLP) and well-matched controls using cone beam computed tomography. Materials and Methods: The study sample consisted of 16 patients (11 female and 5 male; mean [SD] age 14.1 [2.1] years) affected by BCLP and 16 patients (10 female and 6 male; mean [SD] age 13.4 [2.0] years) as age-and sex-matched control group. Craniofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 30 publications
10
48
2
Order By: Relevance
“…Because CBCT has been shown to be a reliable method for assessing dehiscences and fenestrations, we decided to use these images in cleft patients, a technique that has not been reported previously. Consistent with previous studies 4,5,[18][19][20][21][22][23][24] showing the high reliability of CBCT for 2-D and 3-D measurements, agreement was 100% for the detection of dehiscences and fenestrations. Although Sun et al 12 reported that this method might overestimate the actual measurements, the technique was reported to have the highest sensitivity and diagnostic accuracy for detecting various periodontal defects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Because CBCT has been shown to be a reliable method for assessing dehiscences and fenestrations, we decided to use these images in cleft patients, a technique that has not been reported previously. Consistent with previous studies 4,5,[18][19][20][21][22][23][24] showing the high reliability of CBCT for 2-D and 3-D measurements, agreement was 100% for the detection of dehiscences and fenestrations. Although Sun et al 12 reported that this method might overestimate the actual measurements, the technique was reported to have the highest sensitivity and diagnostic accuracy for detecting various periodontal defects.…”
Section: Discussionsupporting
confidence: 79%
“…Their results are consistent with those of the present study, in which the dehiscence rate for centrals on the cleft site was significantly higher than that in the control group (43.2% and 13.7%, respectively). In a study 22 that analyzed these defects in different sagittal malocclusion groups, the incidences of fenestrations for maxillary central incisors were 23.1% in Class I, 18.5% in Class II, and 21.1% in Class III malocclusion patients. In another study 9 that evaluated these defects according to vertical growth patterns, the presence of fenestrations for the same tooth were similar in hyperdivergent (21.1%) and normodivergent (22.4%) groups.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a previous study where the posterior wall of the pharynx was used to delineate the posterior airway margin. 27 Anteriorly, superiorly and inferiorly, identification of the pharyngeal airway margins is much more complicated owing to the close association with mobile soft tissues. 30,36,37 However, hard-tissue points that can be used to develop margins that approximated the softtissue boundaries are easily identifiable ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…• coronal view-so that the most inferior point on the infraorbital margin (orbitale) of both sides lies on the same horizontal plane (Figure 1a Definitions of the new upper airway margins were then proposed according to anatomical margins of the upper airway in children [35][36][37] and previous CBCT studies of children [18][19][20][21][22][23][24][25][26][27] (Table 1). The margins were outlined on the mid-sagittal plane.…”
Section: Airway Assessmentmentioning
confidence: 99%
See 1 more Smart Citation